Assessing Arabic Language Exposure Instrument (I-ALEx) In Higher Education Using The Rasch Measurement Model - Mohd Rushdi, Nur Afiqah Athirah Awwad; Asbulah, Lily Hanefarezan; Lubis, Firuz-Akhtar; Aladdin, Ashinida; Sahrim, Mus’ab (Ijaz Arabi Journal of Arabic Learning, 2025)
Exposure is crucial for language acquisition, yet Arabic language learners in Malaysia face limited exposure. To accurately measure the extent of this exposure among higher education students, the researcher has developed the Arabic Language Exposure instrument (I-ALEx). This study applied the Rasch Model to validate the I-ALEx, which was designed to assess students' exposure to the Arabic language. Data were collected from 374 final-year Arabic language students from eight universities in Malaysia using a cross-sectional survey design. The I-ALEx includes 20 items divided into two sub-constructs: target language and culture, on a four-point Likert scale (strongly disagree to agree strongly). The quality of the items was evaluated using Winsteps version 5.2. The analysis indicated that all items on the I-ALEx satisfied the Rasch model requirements, thereby supporting the reliability and validity of the instrument. This validation supports the I-ALEx as an effective tool for evaluating Arabic language exposure among higher education students, thus enhancing the assessment practices in language education.